Environmental sustainability competency framework for polytechnics engineering programmes - Mukhtar, Nasiru (Institute of Electrical and Electronics Engineers Inc., 2019)
Sustainability challenges such as degradation of ecosystem, loss in biodiversity, depletion and destruction of natural resources, numerous instances of pollution, and the extreme poverty of millions of human beings all originated from how people think. In an effort to improve the situation, the UN declared the years 2005-2014 as Decade of Education for Sustainable Development (DESD), calling for a thorough integration of competencies in sustainability issues at all levels of education. In line with this, addressing numerous sustainability-related problems requires an urgent need to reorient the school curricula, so that appropriate sustainability competencies are injected. Since the contents of HEIs curricula revolve around knowledge-based goals, skill-based goals and affective goals, this study investigated competencies (Knowledge, Skills and Attitudes) in the environmental sustainability suitable for incorporation into Higher National Diploma (HND) electrical/electronic engineering curriculum in Nigeria. The study employed qualitative approach through document analysis and semi-structured interview with the participants. The documents analyzed were twelve Journal Articles and five Skill Standards. The researchers also conducted interviews with electrical/electronic personnel in the academia and industry. The empirical findings of the semi-structured interviews corroborated the theoretical findings in the documents analyses. The study discovered several competencies in the document analysis as well as interviews, which were ultimately analyzed thematically. The themes include: Climate change, Ecology, Environmental Resource Management, System Thinking, Sustainable urbanization, Recycling/Re-use, and Empathy and Ethics. The researchers analyzed only 17 documents and conduct 10 interviews, thus, conclusions derived from these sources rely on the genuineness of the information provided by the participants. The findings provide the researchers, accreditation body as well as curriculum developers with competencies in environmental sustainability in the events of curriculum upgrade or renewal to integrate sustainability. The findings are the results of triangulated data elicited theoretically and empirically.